Assessment of Dental caries status, Periodontal health and oral hygiene practices among two Populations of Moradabad city, India - Amit Tirth; Vipul Yadav; Pradeep S Tangade; TL Ravishankar; Sunil Chaudhary; Anmol Mathur (Occupational Health and Safety Society of Nepal, 2014)
Background: Ever since the beginning of the universe mankind had struggled constantly for their livelihood, Moradabad is branded as the "Brass city" of India, which comprises of a large number of populations working in different industries. Objective: To assess and compare the oral health status of workers employed in brass industries with non industrial workers of Moradabad city. Methods: A total of 500 workers from each group aged 30-50 with 5 years working experience were selected through random sampling. Type III examination was performed by recording who oral health assessment form. To compare the proportion chi-square test was used. Mean values were compared using students t-test. SPSS version 15.0 was used for statistical analyses. Results: The prevalence of dental caries as Mean DMFT score was significantly higher in Non Industrial Group i.e. 3.57±2.74 while it was 2.88±2.14 in brass workers. Periodontal diseases were higher among production workers that belong to brass industries. The prevalence of Oral Mucosal Lesions was significantly higher among Production Workers. Bleeding was more pronounced in general population but calculus and pockets were seen more in brass workers. The requirement of prosthetic status was also more prevalent among industry subjects. Conclusion: The Oral health status of Brass Industry Workers was relatively poor with poor periodontal health when compared to General Population. Further studies of oral occupational disease should be conducted in order to check or confirm previous reports and to discover possible manifestations arising in new industries